A rapid, quantitative, non-radioactive bisulfite-SNuPE- IP RP HPLC assay for methylation analysis at specific CpG sites - El Maarri, Osman (2002)
The precise mapping and quantification of DNA methylation as an epigenetic parameter during development and in diseased tissues is of great importance for functional genomics. Here we describe a rapid, quantitative method to assess methylation levels at specific CpG sites using PCR products of bisulfite-treated genomic DNA. Using single nucleotide primer extension (SNuPE) assays in combination with ion pair reverse phase high performance liquid chromatography (IP RP HPLC) separation techniques, methylated and unmethylated CpGs can be discriminated and quantified based on the different masses and hydrophobicities of the extended primer products. The assay is linear, highly reproducible and several sites can be measured simultaneously in one reaction. It can be semi-automated and eliminates the need for cloning and sequencing of individual bisulfite PCR products.